Sacrospinous ligament fixation: medium and long-term anatomical results, functional and quality of life results - Angeline Favre-Inhofer; Marie Carbonnel; Rouba Murtada; Aurélie Revaux; Jennifer Asmar; Jean-Marc Ayoubi (BMC, 2021)
Abstract Background To evaluate the medium and long-term anatomical results of sacrospinous ligament fixation (SLF) and its impact on quality of life (QoL). Methods We conducted a retrospective and observational single centre study. Fifty-nine patients were interviewed using the Pelvic Floor Distress Inventory and Pelvic Floor Impact Questionnaire and underwent physical examination using POP-Q several years after SLF. Primary outcome was the comparison of anatomic results of SLF at medium-term (group 1: 1-5 years after surgery) and long-term (group 2: more than 5 years after surgery). The secondary outcome was QoL evaluation. Results The overall recurrence and complication rates were respectively 22% and 10%, with no significant differences between groups 1 and 2. The recurrence rate was similar in both groups [twelve (35%) in group 1 and nine (20%) in group 2, p = 0.09]. Two patients (12%) in the recurrence and none in the no recurrence group had clinical symptoms (p = 0.08). Two patients (12%) in the recurrence and one patient (2%) in the no-recurrence group had a significant impact on their quality of life (p = 0.12). Conclusion This study showed sustainable anatomic and functional results of SLF in medium and long-term analysis with overall low morbidity.